Study of Potential Ecotourism in Area Tulang Island Karimun Regency Riau Island Province - B, Arief Rachman; Thasimmim, Said Nuwrun (Jurnal Perikanan dan Kelautan, 2022)
This research was carried out on Tulang Island, Karimun Regency, Riau Islands Province. This research was carried out from February to August 2020. The implementation of this research was carried out because one of the economic potentials in Karimun Regency is tourism and ecotourism. The purpose of this research is to examine the potential of coastal ecotourism, potential of mangrove ecotourism, and potential of fishing ecotourism. This research method uses a mixture of qualitative and quantitative methods. The data collection method uses the observation method namely observing every condition that exists on Pulau Tulang. The results of research on the study of ecotourism potential the beach got the Tourism Suitability Index value of 77.38% with the criteria suiTabel for being made into ecotourism. A study of the potential for mangrove ecotourism, obtained a tourism suitability index value of 84.32% with the appropriate criteria for ecotourism. While the potential for fishing ecotourism is obtained by the Tourism Suitability Index of 96.30% with criteria suitabel for ecotourism and almost reaching a value of 100%, Potential of coastal ecotourism, mangrove ecotourism and fishing ecotourism in Tulang Island very suitabel to be developed.